Elementary School Teachers in Neoliberal Times: The Silent Voices That Make Educational Policies Work - Carmen Helena Guerrero-Nieto; Alvaro Quintero (Universidad Nacional de Colombia, 2021)
This paper aims at showing how a bottom-up approach of the study of educational policies can shed some light on how elementary school teachers deal with educational policies to make them work. This is a partial report on a larger focus group study conducted in Bogotá, Colombia, where a group of elementary school teachers shared their opinions about educational policies. The data collected allowed us to see that teachers take actions, have their own perspectives about policies, and feel negatively treated by the national government, which give way to three categories: Teachers' Micro-Practices, Clashing Visions About Education, and Mistreatment. We conclude that despite the pervasiveness of neoliberalism in education, which teachers are very aware of, they find ways to make policies work while being critical of the way these are designed and implemented.